2016
DOI: 10.1016/j.nano.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD44 receptor-positive lung tumors using polysaccharide-based nanocarriers: Influence of nanoparticle size and administration route

Abstract: Combating cancers remains an important goal in clinical medicine. In this study, the authors investigated the ability of two hyaluronan-based nanoparticles targeting CD44 receptors to home in on lung cancer cells in an in-vivo orthotropic model. The preferential uptake of smaller sized nanoparticles via intravenous route has further enhanced the existing knowledge of future drug designs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 33 publications
8
49
0
Order By: Relevance
“…[11][12][13] In this context, we previously developed glycopolypeptide-based nanocarriers [14][15][16] that combined the natural polysaccharide hyaluronan, known for its relative affinity toward CD44 receptors that are up-regulated on some cancer cells and involved in tumor growth, progression and metastasis, and poly( -benzyl-L-glutamate) (PBLG), a biodegradable polypeptide characterized by an ordered secondary structure (α-helix). [17,18] These nanoparticles (NP) showed active targeting of CD44-overexpressing lung tumor cells in vitro and in vivo, [19] suggesting that they could be used as a targeted drug-delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] In this context, we previously developed glycopolypeptide-based nanocarriers [14][15][16] that combined the natural polysaccharide hyaluronan, known for its relative affinity toward CD44 receptors that are up-regulated on some cancer cells and involved in tumor growth, progression and metastasis, and poly( -benzyl-L-glutamate) (PBLG), a biodegradable polypeptide characterized by an ordered secondary structure (α-helix). [17,18] These nanoparticles (NP) showed active targeting of CD44-overexpressing lung tumor cells in vitro and in vivo, [19] suggesting that they could be used as a targeted drug-delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the particle comprise of single crystal due to the close comparison between XRD results and TEM micrographs. Based on many studies, nanoparticles size of 25-50 nm is the optimum range to avoid RES sequestering and to have a superior cellular uptake [40][41][42][43][44]. Here, the size obtained demonstrated that the nanoparticles size is in this ideal range and has a potential for effective drug and gene transportation.…”
Section: Resultsmentioning
confidence: 73%
“…In order for the nanoparticle to exhibit selectivity for the lung, it is necessary to obtain small nanoparticles, smaller than 10 nm, and the composition of the nanoparticle also becomes important to obtain stable nanosystems that do not present toxicity when administered in the body (33)(34) .…”
Section: Resultsmentioning
confidence: 99%